Remote Activation of a Latent Epitope in an Autoantigen Decoded With Simulated B-Factors - Pang, Yuan-Ping; Casal Moura, Marta; Thompson, Gwen E.; Nelson, Darlene R.; Hummel, Amber M.; Jenne, Dieter E.; Emerling, Daniel; Volkmuth, Wayne; Robinson, William H.; Specks, Ulrich (Frontiers in Immunology, 2019)
Mutants of a catalytically inactive variant of Proteinase 3 (PR3)—iPR3-Val103 possessing a Ser195Ala mutation relative to wild-type PR3-Val103—offer insights into how autoantigen PR3 interacts with antineutrophil cytoplasmic antibodies (ANCAs) in granulomatosis with polyangiitis (GPA) and whether such interactions can be interrupted. Here we report that iHm5-Val103, a triple mutant of iPR3-Val103, bound a monoclonal antibody (moANCA518) from a GPA patient on an epitope remote from the mutation sites, whereas the corresponding epitope of iPR3-Val103 was latent to moANCA518. Simulated B-factor analysis revealed that the binding of moANCA518 to iHm5-Val103 was due to increased main-chain flexibility of the latent epitope caused by remote mutations, suggesting rigidification of epitopes with therapeutics to alter pathogenic PR3•ANCA interactions as new GPA treatments.